(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
The uniqueness of the economy, industry, production and natural resources of the USA and Britain and their position in the world economy reflect the specific features of the country’s development in the last century. It is noteworthy that there is a discrepancy between the positions of countries in international trade in industrial production and the foreign exchange sector on the one hand, and a reduced but very strong position in the export of capital, as well as Washington and London as one of the leading financial and commodity exchange centers. This article will discuss this in detail.